PEMETAAN POTENSI PARIWISATA DAN PEMBANGUNAN MASYARAKAT DALIL BERBASIS FUNGSI HUTAN, KEARIFAN LOKAL DAN TATA KELOLA PEMERINTAH DESA DALIL - Budi Afriyansyah (Jurnal Pengabdian Kepada Masyarakat Universitas Bangka Belitung, 2015)
The responsibility of students is not limited to the academic field of the campus, but also has a responsibility in nation building efforts. Students are required to play an active role in efforts to build the nation through the application of their knowledge in society. The application of this knowledge is expected to be able to bring changes in society towards a better direction. Community development is a form of student service that is in accordance with the Tri Bakti Darma of higher education. The form of student service in building society is in the form of applying their knowledge in the form of work and service.Real Work Lecture (KKN) is one form of student service in the community by applying the knowledge gained on campus to the community. Students are required to use science to solve problems that exist in the community. For students, it is hoped that after KKN, students will gain life skills and soft skills that are useful in the world of work later.The Universitas Bangka Belitung is one of the state universities that carries out Real Work Lectures (KKN) with the theme of organizing Bangka Belitung based on local wisdom. The implementation of this KKN must be carried out professionally and scientifically without having to change the local wisdom that exists in the community. KKN implemented by the Universitas Bangka Belitung is divided into three, namely KKN Kebangsaan, KKN PPM (Community Learning Empowerment) and Thematic KKN. After this KKN, Universitas Bangka Belitung students are expected to be able to build a community that goes hand in hand with the local wisdom that exists in the community.The Community Service Program (KKN) carried out in Dalil Village is Thematic KKN. The title of this Thematic KKN is Mapping Tourism Potential and Dalil Community Development Based on Forest Functions, Local Wisdom and Village Government Governance. Dalil Village has an area of about 66.35 km2. Dalil Village has two places with tourism potential, namely Rimba' Mambang Forest and Bukit Maras Waterfall. The main priority of the implementation of the Real Work Lecture (KKN) in Dalil Village is to pioneer the Rimbe' Mambang Forest as a tourist forest and Bukit Maras Waterfall as a tourist attraction. In addition, it also promotes these attractions to the general public.